SOCIALIZATION OF THE APPLICATION OF HALAL CERTIFICATES FOR MICRO, SMALL AND MEDIUM ENTERPRISES (UMKM)IN UNING TERITIT VILLAGE, BUKIT SUB-DISTRICTBENER MERIAH DISTRICT: SOSIALISASI PENERAPAN SERTIFIKAT HALAL BAGI PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM)DI DESA UNING TERITIT KECAMATAN BUKITKABUPATEN BENER MERIAH - Cut Nelly; Hadi Susilo; Kamaruddin Hasan; Azhar Ishak; Ika Rezvani Aprita (PT. ROCE WISDOM ACEH, 2025)
Uning Teritit Village is located in the Bukit sub-district of Bener Meriah Regency. This village has several MSMEs, especially in the fields of agriculture and plantations. MSME owners still do not know the benefits and objectives of the halal certification process. MSME owners consider the halal certification process complicated due to the lack of information obtained. This activity is expected to provide an understanding of the benefits and importance of halal certificates for MSMEs. This community service activity is a collaboration of lecturers and halal process assistants. This activity consists of the preparation stage and the implementation stage of the socialization of the application of halal certificates and involves 10 MSMEs in Uning Teritit Village. The method used in this socialization is in the form of providing material and discussion. The results of the socialization showed the interest of MSME players to take part in the process of obtaining halal certification as an effort to increase consumer confidence and product quality. This service activity can provide positive value to the development of MSMEs in Uning Teritit Village